HEDGING STRATEGIES IN THE ENGLISH ACADEMIC DISCOURSE - Yu. Lysanets; O. Bieliaieva; T. Purdenko; L. Ostrovska; H. Morokhovets (Проблеми екології та медицини)
The article considers the communicative status of hedging in different genres of the English academic discourse. As a linguistic phenomenon, hedging is associated with the choice of a particular communication strategy, usually aimed at reducing the categorical nature of expressions. Hedging allows authors to limit the degree of reliability or validity of the judgment, to take off responsibility for accuracy of information in a statement, and to avoid critical interpretation. The English language training of researchers and teaching staff at medical universities has become a priority task in higher medical education. Therefore, the aim of the study was to examine and systematize the most common challenges in dealing with hedging linguistic constructions in the English academic discourse. The ability to understand and use hedging phrases correctly is an essential prerequisite of successful communication, intercultural reciprocal understanding and international cooperation in the context of rapid development of integration in Ukraine, which renders the present research relevant. The most commonly used hedging constructions, their significance and contextual role in professional communication have been analyzed. The authors have studied the linguistic features of hedging markers, and the functions of hedging constructions depending on the addresser’s intentions. The material of the research is the corpus of research articles and case reports obtained by the method of continuous sampling from the electronic database of medical publications “PubMed”. The analysis of hedging strategies is important to eliminate possible mistakes and avoid misunderstanding in medical communication. The study of the functional implementation of hedging on the basis of certain academic genres of the English medical discourse specifies the "doctor – patient" communicative situation, motivates the communicative behavior of narrative figures, and optimizes international professional communication. The authors believe that paying due attention to this linguistic phenomenon within the framework of the training PhDs and academic staff will promote scientific cooperation, thus contributing to the development of higher medical education in Ukraine.